A novel way to designing the undergraduate mechanical engineering curriculum using active stakeholder participation - Khot, Sachin B.; Patil, Sachin K.; Kulkarni, Sushma S. (Journal of Engineering Education Transformations, 2025)
Curriculums that are adaptable to the demands of the communities they serve are the most effective. Whether you intend to modify an existing curriculum or develop one from scratch, you must first undertake an evaluation. This article outlines the creative method utilised to develop the new curriculum in accordance with AICTE requirements. The first stage in formulating a plan is to determine the industries where graduates will find work and the skill sets they will require to be successful in those professions. The strategy emphasizes the need of including important stakeholders in curriculum development at an early stage. According to the findings of a survey given to a diverse group of stakeholders, there are issues with the current curriculum as it is assessed. This paper presents a case study of the development of the mechanical engineering curriculum at Tier-I institution from western Maharashtra for undergraduate (UG) students.